Effects of Renal Denervation on Ouabain-Induced Hypertension in Rats - Minna Tang; Jialu Hu; Wenshu Li; Ningzhi Zhang; Sisi Ning; Yan Yan; Zhaoqiang Cui (International Journal of Hypertension)
Background. Ouabain, a Na+, K+-ATPase inhibitor, is elevated in hypertensive patients. Evidence suggests ouabain contributes to hypertension mainly through activation of the sympathetic nervous system (SNS). Renal nerves play a vital role in the regulation of SNS activity, so we hypothesize that renal denervation may attenuate the development of ouabain-induced hypertension. Methods and Results. Forty Sprague-Dawley rats were divided into following groups (n = 10 each): control group (sham surgery plus intraperitoneal saline injection), RDN group (renal denervation (RDN) plus intraperitoneal saline injection), ouabain group (sham surgery plus intraperitoneal ouabain injection), and ouabain + RDN group (RDN plus intraperitoneal ouabain injection). After eight weeks, compared with the control group, rats in the ouabain group exhibited elevated blood pressure (P<0.05), increased plasma epinephrine, norepinephrine, angiotensin II, and aldosterone levels (P<0.05). These indexes could be significantly ameliorated by RDN. RDN also reduced the thickening of aortic tunica media and downregulated the expression of proliferating cell nuclear antigen (PCNA) in the thoracic aorta induced by ouabain. Masson staining and echocardiography showed that myocardial fibrosis and increased left ventricular mass in the ouabain group could be attenuated by RDN. Conclusions. The present study reveals that renal nerves play an important role in the development of ouabain-induced hypertension. RDN could inhibit the pressor effect and the myocardial remodeling induced by ouabain potentially via inhibiting catecholamine release and vascular smooth muscle cell proliferation. Clinical studies are needed to explore whether RDN may exhibit better antihypertensive effects on hypertensive patients with high plasma ouabain levels as compared to those with normal plasma ouabain levels.